2018
DOI: 10.1111/imig.12520
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Consequences of the Refugee Crisis

Abstract: The European Union faced an unprecedented influx of asylum seekers during the 2014–2016 refugee and migration crisis. The admitted refugees pose a critical challenge, but at the same time represent an opportunity for the host countries’ public finances. If the fiscal balance of immigration is positive, then migrants become net contributors to public budgets, helping to alleviate the aging related fiscal burden. However, we argue that this is highly unlikely to happen with refugees entering extensive European w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…At that stage, it could be helpful to inform them not only of the special welfare benefits for entrepreneurs, but of other sources, such as subsidies provided by the Dutch Ministry of Economic Affairs for innovation and sustainable business models. Although Gál (2019) concluded that there is no positive fiscal balance of refugee immigration in European Welfare states, we would like to pose that this is, at least in part, likely the result of the many barriers to entrepreneurship.…”
Section: Conclusion and Recommendationsmentioning
confidence: 92%
“…At that stage, it could be helpful to inform them not only of the special welfare benefits for entrepreneurs, but of other sources, such as subsidies provided by the Dutch Ministry of Economic Affairs for innovation and sustainable business models. Although Gál (2019) concluded that there is no positive fiscal balance of refugee immigration in European Welfare states, we would like to pose that this is, at least in part, likely the result of the many barriers to entrepreneurship.…”
Section: Conclusion and Recommendationsmentioning
confidence: 92%
“…Numerous studies of this kind have been carried out for European countries. These often predict a negative overall scal eect of asylum seeker inows conditional on the truth of the model's assumptions-a literature reviewed by Gál (2019). One major limitation of this evidence for policy formulation is that every model abstracts heavily from the real economy, and the results are sensitive to its countless assumptions in unknown measure.…”
Section: Fiscal Effects Of Asylum Seekersmentioning
confidence: 99%
“…The fifth and last contribution in the Special Section on 'Fiscal Consequences of the Refugee Crisis' by Gal (2018) refers to the recent refugee crisis in Europe and the fiscal impact of an unprecedented influx of asylum seekers during 2014-2016 on the EU. As a result of an empirical literature review, it is demonstrated that the fiscal effects of refugees (or non-Westerners) and the humanitarian obligation to accept refugees seem to be in conflict with the pragmatic economic interesta fiscally beneficial immigration.…”
Section: Overview Of the Key Arguments Raised In This Special Sectionmentioning
confidence: 99%